Induction Chemotherapy Plus Simultaneous Modulated Accelerated Radiation Therapy in Non-operative Hypopharyngeal and Supraglottic Laryngeal Squamous Cell Carcinoma: Long-Term Outcome of a Prospective Phase 2 Study - Cai, Boning; Meng, Lingling; Mo, Jingzi; Xu, Shouping; Qu, Baolin; Liu, Fang; Ma, Lin (Frontiers in Oncology, 2021)
Background: To evaluate the toxicities and long-term outcomes of induction chemotherapy (ICT) plus simultaneous modulated accelerated radiation therapy (SMART) in non-operative hypopharyngeal and supraglottic laryngeal squamous cell carcinoma (SCCH/L). Materials and Methods: This was a prospective phase 2 study. Patients diagnosed with SCCH/L, aged from 18 to 75, staged from III to IVB in accordance with the AJCC 2010 criteria, and refusing surgery were eligible. The patients were treated with 2–3 cycles of docetaxel-cisplatin-based ICT and SMART combined with 2–3 cycles of cisplatin-based concurrent chemotherapy. The prescription dose to the primary tumor and metastatic nodes was 69 Gy in 30 fractions. Acute and late toxicities were assessed according to the established Radiation Therapy Oncology Group/European Organization for Research and Treatment of Cancer (RTOG/EORTC) criteria, and long-term outcomes were analyzed. Results: Between February 2013 and June 2015, 55 newly diagnosed SCCH/L patients were enrolled. No grade 2 or worse acute xerostomia was noted. The incidences of grade 3 acute dermatitis, oral mucositis, and pharyngoesophagitis were 12.7, 3.6, and 12.7%, respectively. The median follow-up time was 48 months (range 5.5–74 months). The main late toxicity was hoarseness or sore throat, with an incidence of 32.7%. The 5-year functional larynx-preservation survival was 51.5%. The 3- and 5-year locoregional control and overall survival were 58.2, 51.5, 63.6, and 54.1%, respectively. Conclusions: The ICT plus SMART with a regimen of 69 Gy/30 F for the treatment of SCCH/L demonstrated acceptable severe toxicity, satisfactory long-term outcomes, and laryngeal function preservation.